The Significance of Discordant Serology in Chagas Disease: Enhanced T-Cell Immunity to Trypanosoma cruzi in Serodiscordant Subjects - Castro Eiro, Melisa D.; Alvarez, María G.; Cooley, Gretchen; Viotti, Rodolfo J.; Bertocchi, Graciela L.; Lococo, Bruno; Albareda, María C.; De Rissio, Ana M.; Natale, María A.; Parodi, Cecilia; Tarleton, Rick L.; Laucella, Susana A. (Frontiers in Immunology, 2017)
Background. Subjects are considered infected with Trypanosoma cruzi when tested positive by at least two out of three serological tests, whereas a positive result in only one of up to three tests is termed “serodiscordant”. Assessment of parasite-specific T-cell responses, may help discriminate the uninfected from infected individuals among serodiscordant subjects. Methods. Peripheral blood mononuclear cells from serodiscordant and seropositive subjects, who were born in areas endemic for Trypanosoma cruzi infection but living in Buenos Aires city, Argentina, at the time of the study, and seronegative unexposed subjects were included for analysis. The function and phenotype of T cells were assessed by IFN-γ and IL-2 enzyme linked immunospot assay and multiparameter flow cytometry. T.cruzi-specific antibodies were quantified by conventional serology and a multiplex assay format. Results. Serodiscordant subjects exhibited immunity cell responses to Trypanosoma cruzi but in contrast to seropositive subjects, T cells in serodiscordant subjects more often display the simultaneous production of IFN-γ and IL-2 in response to T. cruzi antigens and have a resting phenotype. Serodiscordant individuals also have higher IFN-γ spot counts, polyfunctional CD4+ T cells enriched in IL-2 secreting cells and low levels of antibodies specific for a set of T. cruzi-derived recombinant proteins compared with the seropositive group. Long-term follow up of serodiscordant individuals confirmed that humoral and T-cell responses fluctuate but are sustained over time in these subjects. T cells in serodiscordant subjects for T. cruzi infection did not recognize Leishmania antigens. Conclusions. Both T-cell and humoral responses in most subjects assessed by conventional tests as serodiscordant for T. cruzi infection indicate prior exposure to infection and the establishment of immunological memory suggestive of a resolved infection.